Hukum e-Marketplace Auction di Indonesia Sebagai Bentuk Alat Rekayasa Sosial - Sunardi, Arwin Ardianto; Putra, Ido Gustiawan; Adonara, Firman Floranta; Adjie, Habib (Jurnal Ilmiah Penegakan Hukum, 2025)
This study aims to analyze the law of e-Marketplace Auction in PMK No. 122 of 2023 concerning Auction Implementation Guidelines using Roscoe Pound's law as a tool of social engineering. This research is normative juridical type by describing the legal provisions of e-Marketplace Auction in PMK No. 122 of 2023 concerning Guidelines for the Implementation of Auctions. 122 of 2023 concerning Auction Implementation Guidelines with an analytical descriptive approach using Roscoe Pound's law as a tool of social engineering theory. The results of this study indicate that auctions in Indonesia have developed through the use of electronic technology which is regulated in PMK No. 122 of 2023. The enactment of PMK NO. 122 of 2023 is a form of social engineering (tool of social engineering) for the proliferation of auction practices on internet media carried out by the community as a result of technological developments. The enactment of PMK No. 122 of 2023 is a government directive to the public to conduct auctions through e-Marketplace Auction in e-commerce that has been registered with the Indonesian e-commerce association. This requirement is a form of embodiment of Roscoe Pound's theory of law as a tool of social engineering which functions to ensure the protection of public interests (state), society, and each individual so that it can be said that the legal provisions of e-Marketplace Auction in PMK No. 122 of 2023 are a form of legal participation in the process of social change in society.